Facing the Dragons - A Historical-Analytical Study of the Parallels between the Vision of Revelation 12 and Hildegard von Bingen’s Vision of the Antichrist, and their Relevance in Contemporary Society - Ksenafo Akulli (Kairos (English Ed.))
The paper attempts to assess the power of visions in the struggle against injustice. It is argued that the Revelation of John is itself a struggle that advocates for a just spiritual and physical society. The genre of apocalyptic literature, with its symbolic language, and its presence and relevance in Medieval Europe in the writings of Hildegard von Bingen suggest that the power of a vision lies in the capability of the author to detect a problem and creatively provide a solution to emancipate society in the struggle against spiritual and physical injustice.